ALGAL CENOSES IN THE COMMUNITY OF SIX-LINE RICE (F1) AND THEIR MEANING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article was given all details of seaweed flora of rice. Considering the meaning and changing of seaweed bioceonosis depend on vegetation of cultivating rice.
Keywords: algae, cenoses, rice fields, cultivation, reservoirs, fixation.